(4-Chlorobenzohydrazidato-kappa N-2 `,O)[2-(4-chlorobenzoylhydrazinylidene-kappa N-2(1),O)-3-phenylpropionato(2-)-kappa O-1]oxidovanadium(V) methanol monosolvate - Wong, H.W.; Lo, K.M.; Ng, S.W. (International Union of Crystallography, 2010)
The V-V atom in the title compound, [V(C7H6ClN2O)(C16H11ClN2O3)O]center dot CH3OH, is N,O-chelated by the benzoylhydrazidate anion and O,N,O'-chelated by the (benzoylhydrazinylidene) propionate dianion. The distorted octahedral trans-N2O4 coordination geometry is completed by the vanadyl O atom. The mononuclear and solvent molecules are linked by N-H center dot center dot center dot O and O-H center dot center dot center dot O hydrogen bonds about a center of inversion, generating a dimer.